2012
DOI: 10.1002/pd.3843
|View full text |Cite
|
Sign up to set email alerts
|

Fetal varicella – diagnosis, management, and outcome

Abstract: Fetal varicella syndrome (FVS) is due to transplacental infection by the Varicella zoster virus following maternal infection. The risks for the fetus and neonate depend on the timing. When varicella occurs around delivery, it often leads to disseminated neonatal varicella. When varicella occurs during pregnancy, transmission can occur, but is usually asymptomatic; some infants develop zoster postnatally and a few have FVS. Before 20 weeks' gestation, FVS can occur, with an incidence of about 1%. The lesions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 94 publications
(186 reference statements)
0
39
0
3
Order By: Relevance
“…It has been reported that the mortality rate during the first month of life is 30%, but infants who survive this period can have a good long-term outcome even though there is a 15% risk of developing herpes zoster between the fourth and forty-first month of life [26,53,145,147,159,169,170] . CVS is probably due to herpes zoster-like reactivation in utero rather than initial varicella, and this view is supported by the fact that the skin lesions have a dermatomal distribution similar to that of herpes zoster [26,167,171] .…”
Section: Cvsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that the mortality rate during the first month of life is 30%, but infants who survive this period can have a good long-term outcome even though there is a 15% risk of developing herpes zoster between the fourth and forty-first month of life [26,53,145,147,159,169,170] . CVS is probably due to herpes zoster-like reactivation in utero rather than initial varicella, and this view is supported by the fact that the skin lesions have a dermatomal distribution similar to that of herpes zoster [26,167,171] .…”
Section: Cvsmentioning
confidence: 99%
“…The most widely used drug, acyclovir (and its precursor valacyclovir) is a synthetic nucleoside analogue of guanine that is highly specific for cells infected by herpesvirus and does not interfere with human DNA [169] . When phosphorylated by cellular enzymes (thymidine kinases), acyclovir triphosphate inhibits viral DNA synthesis by competing with deoxyguanosine triphosphate as a substrate for viral DNA polymerase.…”
Section: Therapymentioning
confidence: 99%
See 3 more Smart Citations